1996
DOI: 10.1099/13500872-142-6-1335
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of antibiotic production in Streptomyces coelicolor A3(2)

Abstract: The regulation of antibiotic production in Streptomyces coelicolor A3(2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
166
0
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(172 citation statements)
references
References 101 publications
(156 reference statements)
2
166
0
4
Order By: Relevance
“…11,21 We showed that scandium and lanthanum are both effective not only for enhancement of actinorhodin production but also for activation of silent or poorly expressed genes in S. coelicolor. In particular, scandium appears to be a feasible reagent for gene activation because it showed a rather wide range of effective concentrations.…”
Section: Resultsmentioning
confidence: 97%
“…11,21 We showed that scandium and lanthanum are both effective not only for enhancement of actinorhodin production but also for activation of silent or poorly expressed genes in S. coelicolor. In particular, scandium appears to be a feasible reagent for gene activation because it showed a rather wide range of effective concentrations.…”
Section: Resultsmentioning
confidence: 97%
“…Since actinorhodin is produced later in development than undecylprodigiosin (2), this phenotype may be the result of an arrest in development at a time where actinorhodin production has not yet been initiated.…”
Section: Discussionmentioning
confidence: 99%
“…A particular feature of this strain is its production of four antibiotics, all of different chemical classes, allowing analysis of the regulation of antibiotic biosynthesis at different levels. These include pathwayspecific regulation, pleiotropic control of more than one antibiotic, and co-regulation of antibiotic production and morphological development (Bibb, 1996;Chater & Bibb, 1997;.…”
Section: Introductionmentioning
confidence: 99%